Pesticide Residues and Stuck Fermentation in Wine: New Evidences Indicate the Urgent Need of Tailored Regulations - Pasquale Russo; Carmen Berbegal; Cristina De Ceglie; Francesco Grieco; Giuseppe Spano; Vittorio Capozzi (Fermentation, 2019)
For three consecutive years, an Italian winery in Apulia has dealt with sudden alcoholic stuck fermentation in the early stages of vinification process, i.e., typical defects addressable to bacterial spoilage. After a prescreening trial, we assessed, for the first time, the influence of the commercial fungicide preparation Ridomil Gold® (Combi Pepite), containing Metalaxyl-M (4.85%) and Folpet (40%) as active principles, on the growth of several yeasts (Saccharomyces cerevisiae and non-Saccharomyces spp.) and lactic acid bacteria of oenological interest. We also tested, separately and in combination, the effects of Metalaxyl-M and Folpet molecules on microbial growth both in culture media and in grape must. We recalled the attention on Folpet negative effect on yeasts, extending its inhibitory spectrum on non-Saccharomyces (e.g., Candida spp.). Moreover, we highlighted a synergic effect of Metalaxyl-M and Folpet used together and a possible inhibitory role of the fungicide excipients. Interestingly, we identified the autochthonous S. cerevisiae strain E4 as moderately resistant to the Folpet toxicity. Our findings clearly indicate the urgent need for integrating the screening procedures for admission of pesticides for use on wine grape with trials testing their effects on the physiology of protechnological microbes.